2013
DOI: 10.1116/1.4826881
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of trimethylgallium on the ZrB2(0001) surface

Abstract: X-ray photoelectron spectroscopy and reflection absorption infrared spectroscopy (RAIRS) have been used to study the dissociative adsorption of trimethylgallium (TMG) on the ZrB 2 (0001) surface. Spectra were obtained as a function of annealing temperature following TMG exposure at temperatures of 95 and 300 K, and also as a function of TMG exposure for a surface temperature of 300 K. After annealing above 220 K, a significant decrease in the relative concentration of carbon and gallium occurred accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…To achieve this goal, better information on the dissociation temperature and decomposition mechanism of NH 3 and other precursor gases on ZrB 2 (0001) is needed. The present work on molecular adsorption of ammonia at low temperatures therefore complements our recent work on the thermal decomposition of TMG 35 and the higher temperature deposition of N from NH 3 decomposition on the ZrB 2 (0001) surface. 24…”
Section: ■ Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…To achieve this goal, better information on the dissociation temperature and decomposition mechanism of NH 3 and other precursor gases on ZrB 2 (0001) is needed. The present work on molecular adsorption of ammonia at low temperatures therefore complements our recent work on the thermal decomposition of TMG 35 and the higher temperature deposition of N from NH 3 decomposition on the ZrB 2 (0001) surface. 24…”
Section: ■ Introductionsupporting
confidence: 61%
“…It is noteworthy that in the NH 3 /Pt(111) system, the N 1s BE of multilayer ammonia was 0.6 eV higher than that of monolayer ammonia . Also in our recent XPS study of TMG on ZrB 2 , we observed that the C 1s BE of multilayer TMG was ∼0.3 eV higher than that of the surface layer . Therefore, the 401.9 eV peak in Figure a is assigned to multilayer ammonia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The peaks at ∼1118.0 eV and ∼1119.6 eV for the double bilayer are due to GaN and Ga 2 O 3 , respectively [42]. Manandhar et al investigated the dissociation of trimethylgallium on ZrBr 2 (0001) surface and reported a significant shift in Ga binding energy of 1119.0 eV toward lower value of 1118.2 eV as gallium becomes more metallic [43]. The integrated intensity ratios of [Ga-Ga]/Ga Total were found to be 0.35 and 0.24, respectively, for the single and double bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…Although we used the same XPS spectrometer for earlier studies of a ZrB 2 (0001) single crystal using a pass energy of 50 eV, 37,46 the sensitivity and resolution of the spectrometer has degraded with time.…”
Section: Introductionmentioning
confidence: 99%